Analysis of PLS enhancement using permutation index based OFDM-DCSK system over multipath Rayleigh fading channel - Dhuha Hussein Hameed; Fadhil S. Hasan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
This paper presented the performance of physical layer security of permutation index (PI) with modulating bits-based orthogonal frequency division multiplexing differential chaos shift keying system (PIM-OFDMDCSK), the objective behind PIM-OFDM-DCSK is to improve and increase the information rate, spectral, and energy efficiencies. In PIM-OFDM-DCSK, the (M) subcarriers, each carry (n+1) bits. The n bits are index bits utilized to choose one permutation of the chaotic reference. On the receiver, after OFDM demodulation, the correlation is made between the permuted versions of the chaotic reference and the received bearing sequence of data. Then the received bits are assessed by determining the maximum correlator outputs via which the n bits are detected. Then the maximum output correlator sign is utilized to detect the modulating bit. The performance of the PIM-OFDM-DCSK is tested under additive white gaussian noise and multipath fading channel. Furthermore, the bit error rate is derived based on the wiretap system for the proposed PIM-OFDM-DCSK and compared with other DCSK modulations. The results show that the proposed PIM-OFDM-DCSK scheme is promising and competitive compared with other DCSK system, and the best BER performance is as an increase in the value of n and a decrease in the value of β.